INTERNALIZATION OF RELIGIOUS MODERATION PRINCIPLES IN ISLAMIC BOARDING SCHOOL EDUCATION OF TAHFIZUL QUR’AN IN SOUTH SULAWESI - Rosmini, Rosmini; Janna, Sitti Riadil; Amin, Muh. Taufiq (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2022)
This study aims to describe the internalization of religious moderation principles in Islamic boarding school education of Tahfizul Qur’an in South Sulawesi in four districts as research objects, namely Makassar City, Maros, Gowa, and Jeneponto regencies. This study used a phenomenological approach with data collection methods using interviews and Focus Group Discussion. The data were analyzed inductively by presenting meaning, uniqueness, and phenomena. The results of this study indicated that religious moderation in Islamic boarding school education of Tahfizul Qur’an in South-Sulawesi was internalized in two aspects. First, the aspect of the learning process included the formulation of tahfiz material based on the convenience principle starting from memorizing chapter 30 based on curriculum using level, quality, and time. In addition, religious moderation was also internalized in the tahfiz method and evaluation. Second, Islamic boarding schools' mentoring process included giving attention, exemplary, habituation, reward, punishment, controlling, and monitoring. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan internalisasi prinsip moderasi beragama dalam pendidikan pesantren Tahfizul Qur’an di Sulawesi Selatan di empat kabupaten sebagai objek penelitian, yaitu Kabupaten Kota Makassar, Maros, Gowa, dan Jeneponto. Penelitian ini menggunakan pendekatan fenomenologis dengan metode pengumpulan data menggunakan wawancara dan Focus Group Discussion. Data dianalisis secara induktif dengan menyajikan makna, keunikan, dan fenomena. Hasil penelitian ini menunjukkan bahwa moderasi beragama dalam pendidikan pondok pesantren Tahfizul Qur’an di Sulawesi Selatan terinternalisasi dalam dua aspek. Pertama, aspek proses pembelajaran meliputi perumusan materi tahfiz berdasarkan asas kemudahan mulai dari hafalan bab 30 berdasarkan kurikulum dengan menggunakan tingkatan, kualitas, dan waktu. Selain itu, moderasi beragama juga diinternalisasikan dalam metode dan evaluasi tahfiz. Kedua, proses pendampingan pondok pesantren meliputi pemberian perhatian, keteladanan, pembiasaan, penghargaan, hukuman, pengendalian, dan pengawasan.